Oxidative desulfurization of fuel oils-catalytic oxidation and adsorptive removal of organosulfur compounds - Ogunlaja, Adeniyi Sunday (Rhodes University, Faculty of Science, Department of Chemistry, 2014)
The syntheses and evaluation of oxidovanadium(IV) complexes as catalysts for the oxidation of refractory organosulfur compounds in fuels is presented. The sulfones produced from the oxidation reaction were removed from fuel oils by employing molecularly imprinted polymers (MIPs). The oxidovanadium(IV) homogeneous catalyst, [V ͥ ͮ O(sal-HBPD)], as well as its heterogeneous polymer supported derivatives, poly[V ͥ ͮ O(sal-AHBPD)] and poly[V ͥ ͮ O(allylSB-co-EGDMA)], were synthesized and fully characterized by elemental analysis, FTIR, UV-Vis, XPS, AFM, SEM, BET and single crystal XRD for [V ͥ ͮ O(sal-HBPD)]. The MIPs were also characterized by elemental analysis, FTIR, SEM, EDX and BET. The catalyzed oxidation of fuel oil model sulfur compounds, thiophene (TH), benzothiophene (BT), dibenzothiophene (DBT) and 4,6-dimethyldibenzothiophene (4,6-DMDBT), was conducted under batch and continuous flow processes at 40°C by using tert-butylhydroperoxide (t-BuOOH) as oxidant. The continuous flow oxidation process presented the highest overall conversions and very high selectivity for sulfones. Maximum oxidation conversions of 71%, 89%, 99% and 88% was achieved for TH, BT, DBT and 4,6-DMDBT respectively when poly[V ͥ ͮ O(allylSB-co-EGDMA)] was employed at a flow-rate of 1 mL/h with over 90% sulfone selectivity. The process was further applied to the oxidation of hydro-treated diesel containing 385 ± 4.6 ppm of sulfur (mainly dibenzothiophene and dibenzothiophene derivatives), and this resulted to a high sulfur oxidation yield (> 99%), thus producing polar sulfones which are extractible by polar solid phase extractants. Adsorption of the polar sulfone compounds was carried-out by employing MIPs which were fabricated through the formation of recognition sites complementary to oxidized sulfur-containing compounds (sulfones) on electrospun polybenzimidazole (PBI) nanofibers, cross-linked chitosan microspheres and electrospun chitosan nanofibers. Adsorption of benzothiophene sulfone (BTO₂), dibenzothiophene sulfone (DBTO₂) and 4,6-dimethyldibenzothiophene sulfone (4,6-DMDBTO₂) on the various molecularly imprinted adsorbents presented a Freundlich (multi-layered) adsorption isotherm which indicated interaction of adsorbed organosulfur compounds. Maximum adsorption observed for BTO₂, DBTO₂ and 4,6-DMDBTO₂ respectively was 8.5 ± 0.6 mg/g, 7.0 ± 0.5 mg/g and 6.6 ± 0.7 mg/g when imprinted chitosan nanofibers were employed, 4.9 ± 0.5 mg/g, 4.2 ± 0.7 mg/g and 3.9 ± 0.6 mg/g on molecularly imprinted chitosan microspheres, and 28.5 ± 0.4 mg/g, 29.8 ± 2.2 mg/g and 20.1 ± 1.4 mg/g on molecularly imprinted PBI nanofibers. Application of electrospun chitosan nanofibers on oxidized hydro-treated diesel presented a sulfur removal capacity of 84%, leaving 62 ± 3.2 ppm S in the fuel, while imprinted PBI electrospun nanofibers displayed excellent sulfur removal, keeping sulfur in the fuel after the oxidation/adsorption below the determined limit of detection (LOD), which is 2.4 ppm S. The high level of sulfur removal displayed by imprinted PBI nanofibers was ascribed to hydrogen bonding effects, and π-π stacking between aromatic sulfone compounds and the benzimidazole ring which were confirmed by chemical modelling with density functional theory (DFT) as well as the imprinting effect. The home-made pressurized hot water extraction (PHWE) system was applied for extraction/desorption of sulfone compounds adsorbed on the PBI nanofibers at a flow rate of 1 mL/min and at 150°C with an applied pressure of 30 bars. Application of molecularly imprinted PBI nanofibers for the desulfurization of oxidized hydro-treated fuel showed potential for use in refining industries to reach ultra-low sulfur fuel level, which falls below the 10 ppm sulfur limit which is mandated by the environmental protection agency (EPA) from 2015.
Keywords: Organosulfur compounds; Organosulfur compounds -- Oxidation; Organosulfur compounds -- Absorption and adsorption; Petroleum as fuel; Catalysis; Imprinted polymers; Molecular imprinting; Nanofibers; Electrospinning